MISE EN SCÈNE SINEMATOGRAFI DALAM FILM HOROR BERJUDUL PRIMBON BERTEMAKAN KEPERCAYAAN BUDAYA JAWA - Martinus Eko Prasetyo; William Sanjaya (Jurnal Bahasa Rupa, 2025)
Indonesian horror films initially often explore mysterious stories and ghosts from local mythology, creating a mysterious atmosphere enriched with cultural elements such as addressing themes of Javanese cultural beliefs in a film titled "Primbon". Unfortunately, there have not been many studies discussing horror films in terms of Mise en Scène in Indonesia. The film titled "Primbon" is a work of director Rudy Soedjarwo, who is a director and film producer in Indonesia. He is known for his work in the Indonesian film industry. Researchers wanted to determine how important the visual appearance through Mise en Scène is in horror films. This research was conducted descriptively qualitatively, data collected through literature searches on theories related to cinematography and composition in films, using the Kurt Lewin method approach. The research revealed that the Mise en Scène in a horror film like "Primbon" appears slightly different because the impression of the storyline intended to convey is tension, fear, and audience emotional sadness, and this is felt to be very important in building the visual mood. Horror films not only always scare by presenting horror alone, but sadness and pathos can become the climax of a unique and interesting horror film.